Variation of Formant Frequency with Nepalese Vowels - Adhikari, S.K. (BMC Journal of Scientific Research, 2020)
The regions of speech spectrum in which the frequency corresponds to relatively large amplitude are known as formants. For any vocalic sounds, number of formants may occur in the frequency range 0 to 4000 Hz. The formant frequencies of speech sounds are directly depending up on the shape and size of vocal tract. The aim of study was to study the variation of formant frequency with Nepalese vowels. Ten Nepalese vowels word in initial position /VC/ as spoken three times by 10 male and 10 female Nepali speakers were recorded in system in the free field of partially acoustically treated room. PRRAT software is used to digitize and analyze the data. Linear predictive coding (LPC) spectra were obtained for each of vowels and formant frequencies were measured. By plotting curve between formant frequencies and vowels, explain their variation.